Biomechanical Substantiation of the Strength and Stiffness of a Hip Joint Capsule Defect Fixation with Polypropylene Mesh - Maslennikov, S. O.; Panchenko, S. P.; Golovakha, M. L.; Масленніков, Сергій Олегович; Панченко, С. П.; Головаха, Максим Леонідович (My University, 2020)
Formulation of the problem Dislocation of the femoral component of the endoprosthesis is one of the most frequent complications of total hip replacement. The best option for the “treatment” of dislocation of the hip endoprosthesis is to prevent the development of primary instability. There are cases in which even with the correct installation of the endoprosthesis components, dislocations arise due to the weakness or defect of the capsular–ligament apparatus. Currently, many methods have been developed to strengthen and restore the posterior structures of the capsule of the hip joint with the help of auto- and allomaterials, which differ in both the fixation technique and the characteristics of the materials themselves. In this paper, we propose a method for restoring and strengthening the posterior structures of the capsule of the hip joint using polypropylene-based graft implants. The purpose of this study is to, with the help of specialized software, build a model of the capsule of the hip joint after capsulotomy and to determine the stiffness capabilities of the defect covered with polypropylene mesh. Results The study was performed using a software package based on the finiteelement method. As a result of the performed calculations, pictures of the distribution of the stress–strain state in the “head-capsule” system were obtained. To assess the effectiveness of the method of closing the capsule, from the viewpoint of rigidity, as the main characteristics, the values of the opening of the cut are selected. Conclusions Under the kinematic loading of the model, the smallest values of the opening of the section are obtained when it is closed by a grid. In the case of thread fixation, the values were higher by 8.5%. However, the values of equivalent stresses, both in the capsule and in the head, in the model with the grid turned out to be the largest. These stresses were higher by 23.8% in the capsule and by 60.4% in the head than the same values for the thread fixation model. The obtained results indicate that the model with a grid is more rigid in the considered fixation variants.
Keywords: endoprosthesis; hip joint; modeling; polypropylene; total hip arthroplasty